FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH UNTUK MENABUNG PADA PT. BNI (PERSERO) Tbk, CABANG USU MEDAN - Sagala, Roslinda (UNIKA Santo Thomas, 2010)
PT. BNI (Persero) Tbk, USU Medan Branch is one of the government-owned enterprises. The bank collects funds from the public in the form of demand deposits, savings deposits, and channel it back in the form of credit. In this study, the authors focus on research for deposits. Number of clients who deposit funds in 2009-2010 has decreased. From the description formulated the research problem is